Environmental footprint assessment of green campus from a food-water-energy nexus perspective. (October 2018) - Gu, Yifan; Wang, Hongtao; Robinson, Zoe P.; Wang, Xin; Wu, Jiang; Li, Xuyao; Xu, Jin; Li, Fengting
Abstract: Universities not only can be considered as small communities due to their intensive population and their provision of complex services, but also play a vital role in the education system for global sustainable future. Thus, the environmental impacts and green operation of universities has great reference value for the design of sustainable development. In this study, we develop an environmental footprint framework based on life cycle analysis (LCA) to systematically and comprehensively understand how universities interact with the hydrologic cycle, energy resources and climate. Using Keele University in UK as an example, we further quantified the nexus and trade-offs between environmental elements including water, energy, food, waste and carbon emissions. We believe that this method will contribute to the development of footprint assessment and sustainable development, and the findings could serve as reference for policy-makers who are interested in developing green campuses.